Hedgehog inhibition prolongs survival in a genetically engineered mouse model of pancreatic cancer. Issue 10 (30th May 2008) - Feldmann, G; Habbe, N; Dhara, S; Bisht, S; Alvarez, H; Fendrich, V; Beaty, R; Mullendore, M; Karikari, C; Bardeesy, N; Ouellette, M M; Yu, W; et al.
Abstract : Background and aims: Pancreatic cancer is among the most dismal of human malignancies. Current therapeutic strategies are virtually ineffective in controlling advanced, metastatic disease. Recent evidence suggests that the Hedgehog signalling pathway is aberrantly reactivated in the majority of pancreatic cancers, and that Hedgehog blockade has the potential to prevent disease progression and metastatic spread. Methods: Here it is shown that the Hedgehog pathway is activated in the Pdx1-Cre;LsL-Kras G12D ;Ink4a/Arf lox/lox transgenic mouse model of pancreatic cancer. The effect of Hedgehog pathway inhibition on survival was determined by continuous application of the small molecule cyclopamine, a smoothened antagonist. Microarray analysis was performed on non-malignant human pancreatic ductal cells overexpressing Gli1 in order to screen for downstream Hedgehog target genes likely to be involved in pancreatic cancer progression. Results: Hedgehog inhibition with cyclopamine significantly prolonged median survival in the transgenic mouse model used here (67 vs 61 days; p = 0.026). In vitro data indicated that Hedgehog activation might at least in part be ascribed to oncogenic Kras signalling. Microarray analysis identified 26 potential Hedgehog target genes that had previously been found to be overexpressed in pancreatic cancer. Five of them, BIRC3, COL11A1, NNMT, PLAU and TGM2, had been described as upregulated in more than one global gene expression analysis before. Conclusion: This study provides another line of evidence that Hedgehog signalling is a valid target for the development of novel therapeutics for pancreatic cancer that might be worth evaluating soon in a clinical setting.